BANKRUPTCY PREDICTION ANALYSIS OF MANUFACTURING COMPANIES CONSUMER GOODS INDUSTRY SECTOR USING ALTMAN Z-SCORE METHOD DURING THE COVID-19 PANDEMIC - Nita Fitria; Helmalia Putri; Khoirulis Shabirin; Oumar Tidiane Doumbouya (Imara: JURNAL RISET EKONOMI ISLAM, 2022)
The main problem in this thesis is that during the Covid-19 pandemic in 2020 the company experienced a decline in sales and company profits also decreased and some even experienced losses, and the company's total debt increased, this led to the factors that led to the company's bankruptcy. The purpose of this study was to determine the prediction of company bankruptcy before the pandemic and during the pandemic using the first Altman Z-Score model. The type of research used is descriptive research. The research method used is quantitative. Data collection techniques through documentation in the form of financial reports of eleven companies engaged in the Consumer Goods Industry Sector listed on the IDX for the 2017-2020 period through the official website www.idx.co.id. The data analysis technique used the first model Altman Z-Score method. The results of research that have been conducted on eleven companies engaged in the Consumer Goods Industrial Sector listed on the IDX in the 2017-2020 period, namely the period before the pandemic and during the Covid-19 pandemic using the Almant Z-Score method, obtained the following results: First, companies that are not affected by the pandemic are PT. HM Sampoerna Tbk and PT. Bantoel International Investama Tbk, and PT Sariguna Primatirta Tbk. Second, the companies affected by the pandemic are PT. Kino Indonesia Tbk, PT. Akasha Wira International Tbk, PT. Campina Ice Cream Industri Tbk, PT. Prima Cakrawala Abadi Tbk. Third, for other companies, namely PT. Merck Tbk, PT. Martina Berto Tbk, PT. FKS Food Sejahtera Tbk, and PT. Kedaung Indah Can Tbk was in a dangerous zone in the period before the pandemic and during the pandemic